Evaluation of effectiveness of Aflatoxins on nutritive value of broiler rations - S. M. Abu-Tabigh (Journal of Madenat Alelem University College, 2010)
To verify effects of Aflatoxins on Broiler rations, two experiments were established . In 1st one ,ten local forage storages in Baghdad were qualitatively evaluated .In the 2nd one ,uncontaminated & contaminated Corn seed meals were qualitatively also evaluated . The results confirmed that 50% of local forage storages were contaminated by Aflatoxins.The results of nutritional values of broiler were also affected . The crude protein and Oil content were significantly reduced from 20.3 to 17.0 & from 2.7 to 1.8 % Meanwhile , crude fiber generally increased from 2.1 to 3.0% , we conclude that Aflatoxins are more veridical affected upon nutritional values of broiler rations & human health.